CHARACTER BUILDING BY MEANS OF TRADITIONAL ARTS - Victor Ganap (International Conference on Languages and Arts, 2014)
Indonesia has been blessed with a rich cultural heritages that consequently needs to be preserved and developed by the existing and future generations. The arts education is believed to have a strategic potential in labouring human resources, who would be able in return to appreciate the arts, and to maintain cultural identity. In capacity as a corroboration of such an exegesis theory, the aforesaid figure may possess a courtesy behavior in society, as to respect the traditional values, to peacefully stepping on the heavenly stairways toward global competition, in terms of the ability to earn living through their art-works creativity. Discourse on arts education in public school will naturally implement a unique learning process described in the local contents, where students imitate the instruction and obtain the esthetical experience in making the arts into practice. It is for that reason, an adequate learning process in arts requires not only the knowledge and skill alone, but the esthetical sincerity as well, in which students will have the opportunity to develop their own personal styles, based on the values of their cultural heritages. Therefore, the esthetical experience within a traditional culture for all generations is a conditio sine qua non to strive for a nation and character building. Keywords: Character building, traditional arts, cultural heritage